Valor preditivo de exames pré-operatórios em facectomias - Lira, Rodrigo Pessoa Cavalcanti (2003)
OBJECTIVE: To establish the prevalence of abnormal results in routine preoperative tests prior to facectomies and whether they influence the occurrence of perioperative clinical complications. METHODS: This prospective study was developed in an academic medical center in Brazil. Besides a clinical evaluation, all patients were requested to undergo an electrocardiogram, complete blood work and fasting blood glucose test. Patients younger than 40 years of age who had had previous eye surgery, candidates for general anesthesia or who had suffered acute myocardial infarction up to three months before surgery were excluded from the study. Intraoperative medical events were recorded in a protocol form. Analysis was carried out using Fisher's test and ANOVA (analysis of variance). RESULTS: The sample was composed of 746 patients, 405 (54.3%) were men. The average age was 66.6±11.6 years. Intraoperative complications occurred in 71 (9.5%) patients. There were abnormal results in 13.5% (101 patients) of hemoglobin dosages and in 16.6% (124) of fasting blood glucose. As for electrocardiograms, abnormalities were found in 46.6% (348) of the subjects. There was a higher prevalence of electrocardiograms with abnormal values in patients who had perioperative clinical complications (p=0.02). There were no statistically significant differences between hemoglobin dosages (14.0±1.6 g/dL in patients without intraoperative complications and 14.3±1.3 g/dL in patients with complications - p=0.150) and fasting blood glucose (104±29 mg/dL in patients without complications and 105±41 mg/dL in patients with complications - p=0.850). CONCLUSIONS: Within the investigated routine of preoperative testing for facectomy, only the abnormal electrocardiogram results influenced the occurrence of complications in the perioperative period.